Actinomycetes isolated from beehives in Thailand - Yaowanoot Promnuan (2018)
Actinomycetes are one of the main microbial groups that produce bioactive compounds used as antibiotics. Although bacteria, mold and yeast have frequently been found in bees, the presence of actinomycetes in bee hives had not been previously identified or reported. The aim of our research was to focus on the diversity of actinomycetes in bee hives in Thailand. Bees, brood cells and hive materials were collected from apiaries and natural sources. Thirty-two isolates of actinomycetes were isolated and identified using morphological, physiological, chemical and molecular characterization. Most of the isolates belonged to the genus Streptomyces. Some less frequent isolates were classified in the genera Nonomuraea, Nocardiopsis and Actinomadura. © 2009 Springer Science+Business Media B.V.